An Analysis of Laser Therapy for the Treatment of Nonmelanoma Skin Cancer. Issue 5 (May 2017) - Soleymani, Teo; Abrouk, Michael; Kelly, Kristen M.
Abstract : BACKGROUND: Skin cancer remains the most prevalent type of cancer in the United States, and its burden on the health care system remains substantial. Standard treatments such as cryosurgery, electrodessication and curettage, topical and photodynamic therapies, and surgical excision including Mohs micrographic surgery are not without inherent morbidity, including risk of bleeding, infection, and scar. OBJECTIVE: Lasers may be an alternative for treatment of nonmelanoma skin cancer, and this paper reviews this therapeutic option. METHODS: A comprehensive search in the Cochrane Library, MEDLINE, and PUBMED databases was performed to identify relevant literature investigating the role of laser therapy in the treatment of nonmelanoma skin cancer. RESULTS: New literature regarding laser treatment of nonmelanoma skin cancer is emerging, demonstrating promising clinical outcomes. The greatest efficacy has been seen with vascular-selective and ablative lasers in the treatment of basal cell carcinomas. Some success has been reported for laser treatment of squamous cell carcinoma, but data are less convincing. In summary, laser therapy offers an alternative treatment option for nonmelanoma skin cancer; however, its clinical efficacy is variable and, at this time, remains less than currently accepted standards of care. CONCLUSION: Further studies are needed to optimize parameters, determine maximum efficacy, and provide long-term follow-up.